The Rise of Magic in Early Medieval Europe - Flint, Valerie I. J. (Valerie Irene Jane), 1936-2009 (Book collections on Project MUSE., 1991)
"There are forces better recognized as belonging to human society than repressed or left to waste away or growl about upon its fringes." So writes Valerie Flint in this powerful work on magic in early medieval Europe. Flint shows how many of the more discerning leaders of the early medieval Church decided to promote non-Christian practices originally condemned as magical - rather than repressing them or leaving them to waste away or "growl." These wise leaders actively and enthusiastically incorporated specific kinds of "magic" into the dominant culture not only to appease the contemporary non-Christian opposition but also to enhance Christianity itself.